Prototype Design of Mobile Application 'Hydrolite' for Hydroponics Marketplace - Salsabila Ramadhina; Angga Aditya Permana; R Taufiq (Proceeding of the Electrical Engineering Computer Science and Informatics, 2020)
Hydroponics is one of the effective farming methods to apply in big cities because it does not require extensive agricultural land. In addition, hydroponic products are cleaner, higher quality and free from pesticides. However, the development of hydroponic products in Indonesia is relatively slow. One of the factors causing the slow development of hydroponic agribusiness is that online sales media for hydroponic products are still limited, especially android-based e-marketplace application. Hydrolite is present as an e-marketplace that specifically sells vegetables grown using the hydroponic method, and sells all the equipment needed to farm hydroponically. Hydrolite is a prototype e-marketplace application designed using the Marvelapp platform. Further, Marvelapp is one of the best prototyping tools to support application development on mobile devices.